ANALYSIS OF THE TOURISM INDUSTRY BUSINESS MODEL WITH THE BUSSINES MODEL CANVAS (BMC) APPROACH IN AN ISLAMIC BUSINESS PERSPECTIVE: Study on Pahawang Island Tourism Village, Marga Punduh District, Pesawaran Regency, Lampung - Saskia, Elsa; Zuliansyah, A; Susanto, Is (Ad-Deenar: Jurnal Ekonomi dan Bisnis Islam, 2025)
Tourism is currently a major development in the Indonesian industrial sector. Indonesia has abundant natural resources and beauty that is very valuable in the natural tourism industry, especially in the tourism sector. Tourism has an important role in the development of Indonesia, namely as a foreign exchange earner. The development of sustainable tourism (sustainability of ecotourism) is influenced by several aspects such as the level of community habits and attitudes towards their environment, the level of government policy support in tourism development, knowledge about environmental conservation itself, and the responsibilities of the parties involved (stakeholders). Development strategies are very important, especially in protecting tourists, providing the facilities needed and the comfort of visitors and the availability of access routes to locations and safe and comfortable infrastructure, in addition to achieving all tourism development goals, promotions must be held so that tourist attractions can be better known and able to drive potential tourists to visit and enjoy tourist attractions. In this case, the Business Model Canvas (BMC) is an effective tool for designing, developing, and analyzing innovative and sustainable business models. BMC covers various important aspects in business decision making, such as identifying market segments, value propositions, resource structures, key activities, customer relationships, and supplier relationships. Identification of this business model strategy must also be in accordance with Islamic business guidelines.